Hypothalamic circuits for female social behaviour - Dias, António José da Silva (2022)
"To engage in adaptive social interactions, animals must be able to recognize chemosignals released by conspecifics. This is especially relevant during sexual behaviour, where the outcome of such interactions can have an important impact in the reproductive fitness of the individual. In rodents, the hypothalamus has been extensively implicated in the control of sociosexual behaviours."